Applications + Practical Conceptualization + Mathematics = fruitful Innovation Proceedings of the Forum of Mathematics for Industry 2014 - Anderssen, Robert S.; Broadbridge, Philip; Fukumoto, Yasuhide; Kajiwara, Kenji; Takagi, Tsuyoshi; Verbitskiy, Evgeny; Wakayama, Masato (Mathematics for Industry,, 2016)
This book is a collection of papers presented at the conference "Forum Math-for-Industry 2014" for which the unifying theme was "Applications + Practical Conceptualization + Mathematics = fruitful Innovation" in October 2014. This epigram encapsulates the dynamics of the process that takes an application through to an innovation. Industrial mathematics can be viewed as the causal engine that implements the epigram by taking an Application such as input and convolving it with a mixture of Practical Conceptualization and Mathematics to generate a fruitful Innovation as output. The book illustrates various aspects of the two-way interaction between applications and their association highlighting how practical conceptualization assists with the linking of the question that encapsulates the current application to the relevant mathematics. The contents of this volume address productive and successful interaction between industry and mathematicians, as well as the cross-fertilization and collaboration that result when mathematics is involved with the advancement of science and technology.